AICCRA Scaling Vision: Ethiopia - Scaling and Scalability: Concepts, Frameworks, and Impact Pathways - Solomon, Dawit; Ambaw, Gebremedhin (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Effective scaling up is a key measure of success for these innovations. Too often, however, the decision to scale up is made with incomplete information. Given the high costs involved, decision-makers (governments, development partners, NGOs, and the private sector) must carefully decide which innovations are ready for investment. A good understanding of the scaling-up process and a conceptual framework that informs the scaling vision, analysis of the scaling readiness of innovations, and impact pathways to achieve that vision are critical for informed decision-making. AICCRA Ethiopia is promoting the broader adoption of Climate information systems (CIS) and climate-smart agriculture (CSA) technologies through a series of pilot projects across a minimum of five major work streams.